From Classroom to Courtroom: Using Role-Plays to Develop Sociolinguistic Competence in English Among Students of Legal Studies - Abdurakhmonova, Dilnoza (Indonesian Journal Publisher, 2025)
The development of sociolinguistic competence is an essential component of legal English instruction for students of legal studies. Future legal professionals must demonstrate not only accuracy in terminology but also the ability to adapt language use to specific institutional and social contexts. This paper examines the role of role-plays – particularly courtroom simulations and client counselling activities – in enhancing sociolinguistic competence within a Content and Language Integrated Learning (CLIL) framework. Theoretical foundations are drawn from models of communicative competence (Hymes, 1972; Canale & Swain, 1980) and sociolinguistic research in legal discourse (Gibbons, 2003; Tiersma, 1999). The integration of role-plays into the legal English classroom provides authentic opportunities for learners to practice register variation, politeness strategies, and pragmatic appropriateness. In addition, the use of information and communication technologies (ICT), including virtual moot courts and multimedia legal resources, extends the authenticity of classroom simulations. International research and empirical findings confirm that role-plays significantly improve students’ pragmatic awareness and professional readiness in multilingual legal environments (Bygate, 2015; Coyle, Hood, & Marsh, 2010).